2019
DOI: 10.12659/msm.914405
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Bone Mineral Density Using Cone Beam Computed Tomography in Patients with Ectodermal Dysplasia: A Retrospective Study at a Single Center in Turkey

Abstract: Background The aim of this retrospective study was to compare the measurements of bone mineral density (BMD) combined with volumetric dental tomography measurements taken from three main regions selected on the lower mandible, the right mandibular, medial mandibular, and left mandibular regions, in patients with ectodermal dysplasia and age-matched and gender-matched controls. Measurement of BMD in Hounsfield units (HUs) were evaluated using three-dimensional (3D) cone beam computed tomography (CB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…CBCT has also been proven to be an appropriate tool for evaluating the maxillary and mandibular bone marrow density [ 24 , 25 , 26 ] and condylar volume [ 27 ]. Thus, further exploring the feasibility of the current segmentation and superimposition protocol for assessing mandibular bone marrow density and tracking condyle modeling and remodeling is the next objective of our investigation.…”
Section: Discussionmentioning
confidence: 99%
“…CBCT has also been proven to be an appropriate tool for evaluating the maxillary and mandibular bone marrow density [ 24 , 25 , 26 ] and condylar volume [ 27 ]. Thus, further exploring the feasibility of the current segmentation and superimposition protocol for assessing mandibular bone marrow density and tracking condyle modeling and remodeling is the next objective of our investigation.…”
Section: Discussionmentioning
confidence: 99%
“…An interested fact was noted during study on 16 children with ED, i.e., bilateral teeth agenesis pattern, which was observed on maxilla with nearly 94% frequency and on mandible with 75% frequency, while greater percentage of missed teeth was observed on mandible [15]. Mean number of missed permanent teeth among males (22) was greater compared to females (4) [4]. Considering such data, it was emphasized that oligodontia itself could be used as an identification marker, which could suggest the presence of ED [16].…”
Section: Oral and Dental Signs Of Ectodermal Dysplasiamentioning
confidence: 88%
“…In a retrospective study, it was shown that among 19 analyzed ED cases, 100% of patients presented with insufficient thickness of alveolar ridge [21]. Bone mineral density evaluation of mandible among ED patients using a Hounsfield unit, revealed a statistically lower value compared to healthy control group [22]. These findings could be used not only as criteria for ED diagnostics, but could be applied during treatment planning of ED patients in prosthetics design with respective support for dental implants.…”
Section: Oral and Dental Signs Of Ectodermal Dysplasiamentioning
confidence: 93%
“…However, as far as the current results are concerned, important adjustments need to be made to the ML model. CBCT images combined with ML models can also be used to measure the bone mineral density of the implant area ( Çolak, 2019 ; Dahiya et al, 2018 ), evaluate the bone mass of the surgical area ( Suttapreyasri, Suapear & Leepong, 2018 ) and assist in the construction of a static guide plate system ( Lin et al, 2020 ).…”
Section: Applications Of ML In the Dental Oral And Craniofacial Imaging Fieldmentioning
confidence: 99%